Pengaruh Air Perasan Umbi Bawang Merah (Allium ascalonicum L.) terhadap Malondialdehid (MDA) Plasma Mencit yang diinduksi Hiperkolesterolemia - Ismawati, Ismawati; Asni, Enikarmila; Hamidy, M Yulis (Jurnal Natur Indonesia, 2012)
Malondialdehyde, a product of lipid peroxidation, is often used as an indicator to detect the oxidative stress damaged in the body. Lipidperoxidation is associated with progression of atherosclerosis. It is known that onion (Allium ascalonicum L.) can be used as an antioxidantand hypolipidemic agent, but whether onion can decrease hypercolesterolemia mice MDA plasma induced by yolk is still unknown. Thepurpose of this study was to investigate the effect of onion’s juice on hypercolesterolemia mice MDA plasma level. This was an experimentallaboratory research with post test only design with control. The measured parameters were cholesterol and MDA level on tested groups.Groups with treatment consist of yolks group, and 80% shallot juice, simvastatin and aquadest were separately used as positive and negativecontrol. The result showed that there was significant difference between high fat feed group which added 80% onion’s juice and high fat feedgroup only. Addition of 80% onion’s juice in high fat feed groups decreased MDA plasma level equal to normal feed group. In conclusion, itwas proved that onion’s juice decreased mice MDA plasma level.